C-2, N-dimethylbenzylamine cyclopalladated compounds: evaluation of cytotoxic, mutagenic and antitubercular activities - Moro, Antonio Carlos [UNESP]; Cunha, Gislaine Aparecida da [UNESP]; Freire de Souza, Ronan Farias [UNESP]; Mauro, Antonio Eduardo [UNESP]; Godoy Netto, Adelino Vieira de [UNESP]; Carlos, Iracilda Zepponi [UNESP]; Resende, Flavia Aparecida [UNESP]; Varanda, Eliana Aparecida [UNESP]; Pavan, Fernando Rogerio [UNESP]; Fujimura Leite, Clarice Queico [UNESP] (Springer, 2015)
Mono- and binuclear cyclometallated Pd(II) compounds containing C,N-chelating dimethylbenzylamine (Hdmba) have been synthesized aiming at investigating their mutagenic properties (Ames test) and cytotoxic activity toward murine tumor cell lines and Mycobacterium tuberculosis. By reactions of [Pd(C (2) ,N-dmba)(mu-X)](2) {X = Br (1), I (2)} with thiourea (tu), in the 1:2 molar ratio, the mononuclear compounds [Pd(C (2) ,N-dmba)(X)(tu)] {X = Br (3), I (4)} were readily obtained. The new compound 4 was characterized by elemental analyses, infrared (IR) and H-1- and C-13{H-1}-NMR spectroscopies. The cytotoxicity assessment of the cyclopalladated compounds 1-4 revealed that the iodo-derivative 4 was the most active toward murine mammary adenocarcinoma (LM3) cells, even more effective than cisplatin. The cyclometallated compounds 1-4 did not demonstrate mutagenic potential according to Ames test results. Compound 4 was only moderately active (MIC = 60 mu g mL(-1)) against M. tuberculosis.Mono- and binuclear cyclopalladated compounds have been synthesized. These complexes displayed cytotoxic levels toward murine mammary adenocarcinoma cells comparable to cisplatin. Cyclopalladated compounds were non-mutagenic in the Ames test, contrary to cisplatin and its analogues.
Keywords: Cyclopalladated complex; Cytotoxicity assays; Tuberculosis; Ames test; Thiourea